Motivating Cypriots to reduce food waste in households through motion graphics video - Christou, Andria (Department of Multimedia and Graphic Arts, Faculty of Fine and Applied Arts, Cyprus University of Technology, 2017)
Food waste is one of the major worldwide problems with an increase trend. At the same time there are approximately “two billion people suffering from hunger and malnutrition worldwide with about 21.000 people dying everyday due to hunger related causes”. Based on the Food and Agriculture Organization known as (FAO) almost “1.3 billion tons of food per year” is being wasted. With such a big amount of waste we could feed all the people that are suffering from hunger. (GHOSH, SHARMA, HAIGH, EVERS, & HO, 2015). All this wastage that happens not only affects the food chain, but it also affects the environment, the economy and the society. These problems are mostly arising from the industrialized countries and induce the way “production, financial, technical, managerial resources are operated”. (Secondi, et. al, 2015). However; most of the wastage is occurring because of “the cultural, social or economic decisions made by producers and lastly consumers” (Secondi, Principato, & Laureti, 2015). Consumers is the main reason why there is a big amount of food loss as the biggest part of waste comes from the household. More specifically it is estimated that 40% of food wasting comes from the domestic section. The consumers are causing this food waste because of their “lifestyle, cooking habits and socioeconomic condition”.(Iacovidou, Ohandja, Gronow, & Voulvoulis, 2012). In small countries like Cyprus there is a huge amount of food waste section especially in household units. This is due to the lifestyle and culture of Cypriots. Countries from the Mediterranean area of the world are most likely closer to their families because they live in small communities (Zorpas, et. al, 2015). This research is focused particularly in the case of Cyprus. As a community, Cypriots are not aware of how to reduce food waste in the household because of their lifestyle (Zorpas, Lasaridi, Voukkali, Loizia, & Chroni, 2015). Cooking is vital for Cypriot families as it is the main way of coming all together, although this is how food waste starts off: cooking a large amount of food, three to four different servings of food per day or throwing away leftovers. My aim is to share the acknowledgment on this cultural issue that comes from the household section in Cyprus, by raising awareness through different facts that might help them understand the consequences of their actions (Georgas1997.Pdf. (n.d.). Through this research it is evident that consumers preferred watching a video instead of a printed work. Thus it would be more influential to express these problems by creating a motion graphic video and to share the acknowledgement about food waste, more specifically in the households.
Keywords: Food waste; Food loss; Food waste in household; Food waste in Europe; Food waste worldwide; Food waste reduction; Food waste problems; Food waste and social impact